Gait Analysis and Simulation of a Multi-mode 4-UPU Mechanism - Bing Ding; Chunyan Zhang; An Ping; Xinyue Yu (Jixie chuandong)
In order to adapt to various environmental requirements， a new multi-mode mechanism with series-parallel switching function is proposed. The mechanism can change its structural constraints according to the actual working conditions to form different modes to improve the motion adaptability of the mechanism. The screw theory is used to analyze the degree of freedom of the mechanism and describe the switching strategy of each mode. The gait of each mode of the mechanism is analyzed， and a simulation experiment of the mechanism gait is carried out using Adams software to verify the feasibility of gait. Finally， the entity modeling of the mechanism and the practicability of the mechanism are discussed.